2012
DOI: 10.1089/acm.2011.0389
|View full text |Cite
|
Sign up to set email alerts
|

Oral Chinese Herbal Medicine for Improvement of Quality of Life in Patients with Stable Chronic Obstructive Pulmonary Disease: A Systematic Review

Abstract: While the results of CHM on HRQoL for stable COPD sufferers were promising, they need to be interpreted with caution due to methodological problems, which should be addressed in future trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 19 publications
(23 reference statements)
2
26
0
1
Order By: Relevance
“…Using Chinese medicines or integrated Chinese and Western medicines to treat stable COPD has significant efficacy [6], improving pulmonary function and increasing diaphragm muscular tension [7]. A large amount of high-quality and high-level evidence has shown that its efficacy in improving symptoms, reducing exacerbations, and improving exercise capacity and quality of life is better than treatment with Western medicines alone [810]. …”
Section: Introductionmentioning
confidence: 99%
“…Using Chinese medicines or integrated Chinese and Western medicines to treat stable COPD has significant efficacy [6], improving pulmonary function and increasing diaphragm muscular tension [7]. A large amount of high-quality and high-level evidence has shown that its efficacy in improving symptoms, reducing exacerbations, and improving exercise capacity and quality of life is better than treatment with Western medicines alone [810]. …”
Section: Introductionmentioning
confidence: 99%
“…Among these herbs include those that have been described to possess anti-infective properties [9-11]. Traditionally, most of these herbal-based medications are dispensed in aqueous forms, and be administered orally [12]. Given the availability of huge number of traditionally used medicinal plants, it is likely that at least a few of these would exhibit antiviral activities at concentrations suitable for direct consumption [13].…”
Section: Introductionmentioning
confidence: 99%
“…(31) Low concentration coix seed oil can excite in vitro frog hearts, while high concentrations regulate the central nervous system and improve anxiety and depression. (32) In conclusion, RA treatment should not just focus on joint lesions. The psychological health and quality of life of patients should also be considered.…”
Section: Discussionmentioning
confidence: 99%